2015
DOI: 10.1016/j.jfa.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Commuting Toeplitz operators on bounded symmetric domains and multiplicity-free restrictions of holomorphic discrete series

Abstract: For any given bounded symmetric domain, we prove the existence of commutative C * -algebras generated by Toeplitz operators acting on any weighted Bergman space. The symbols of the Toeplitz operators that generate such algebras are defined by essentially bounded functions invariant under suitable subgroups of the group of biholomorphisms of the domain. These subgroups include the maximal compact groups of biholomorphisms. We prove the commutativity of the Toeplitz operators by considering the Bergman spaces as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…Commutative families of Toeplitz operators and representation theory. In this section we briefly review some of the results in [4] which connect commutativity of Toeplitz operators with representation theory, in particular restriction of the discrete series representation π λ to subgroups of G or G.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…Commutative families of Toeplitz operators and representation theory. In this section we briefly review some of the results in [4] which connect commutativity of Toeplitz operators with representation theory, in particular restriction of the discrete series representation π λ to subgroups of G or G.…”
Section: 2mentioning
confidence: 99%
“…For instance, in [4] it was shown that if H ⊂ G is a subgroup such that the restriction π λ | H is multiplicity-free, then the Toeplitz operators over the weighted Bergmann space H 2 λ (B n ) with H-invariant symbols form a commuting family. Many examples of subgroups H ⊂ G that give rise to multiplicity-free restrictions can be found using the method of visible actions developed by Kobayashi (see [10,11,12]; the earlier paper [7] by Faraut and Thomas was also important in the development of this theory).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposition 4.6 (DQO [1]). For a given bounded symbol ψ ∈ L ∞ (D) and a fixed λ > p − 1 the following conditions are equivalent (1) The symbol ψ is radial.…”
Section: Analysis On Bounded Symmetric Domainsmentioning
confidence: 99%
“…This is particularly so given the abundance of commutative algebras generated by Toeplitz operators on complex spaces. With this respect, the results from [1] have special relevance as they prove the existence of nontrivial commutative C * -algebras generated by Toeplitz operators on every weighted Bergman space over every irreducible bounded symmetric domain. The first fundamental ingredient to prove the latter is one which has become very important for Toeplitz operators in the last years: group theory.…”
Section: Introductionmentioning
confidence: 99%